Research Progress on using Omics Technology to Examine the Antimicrobial Mechanisms of Natural Active Substances - Zeng, Chaoyi; Tandhanskul, Atittaya; Krungkaew, Samatcha; Likhanapaiboon, Tanawan; Kasayapanan, Witthawat; Yasurin, Patchanee; Tang, Jie; Phusantisampan, Theerawut; Tawai, Atthasit (Applied Science and Engineering Progress, 2025)
Pathogenic microbial metabolism during food storage can lead to food spoilage, which can cause food poisoning and foodborne infections, posing a significant risk to human health and safety. Additionally, food spoilage generates greenhouse gases, which could contribute to global warming and have significant impacts. These challenges prompt us to explore effective solutions to reduce food spoilage, aiming to mitigate its adverse impacts. Many secondary plant metabolites have been used in the food and pharmaceutical industries due to their natural antimicrobial activity and low drug resistance. However, the reported targets of antibacterial action are complex, and with the continuous development of research methods, it has become possible to deeply analyze the antibacterial mechanisms using omics technologies. This article discussed the trends and application of transcriptomics, metabolomics, and proteomics in investigating the antimicrobial and antifungal properties of essential oils (EOs) and their active ingredients, aiming to provide a theoretical basis for the use of plant EOs and their active ingredients in addressing health risks and environmental challenges posed by food spoilage.